2019
DOI: 10.1002/lary.28108
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral sinonasal disease: Considerations in differential diagnosis and workup

Abstract: Objective Imaging findings play an important role in the workup and diagnosis of sinonasal disease. Unilateral versus bilateral involvement is a key finding that can differentiate between various diagnoses. Our objective is to characterize presenting symptoms, imaging findings, and most common diagnoses associated with unilateral versus bilateral sinonasal disease. Methods Patients who underwent surgical intervention for sinonasal disease at Emory University between May 2015 and December 2016 were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…To rule out the primary headache and similar disorders, such as myofascial pain and temporomandibular joint pain, an accurate history and physical exam are needed. Chronic dental infection, foreign body, and both benign and malignant sinonasal neoplasia must be included in the differential diagnosis of unilateral CRS 539 . S 1 Most of these conditions can be eliminated by a thorough physical exam including nasal endoscopy along with appropriate imaging (CT or MRI).…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…To rule out the primary headache and similar disorders, such as myofascial pain and temporomandibular joint pain, an accurate history and physical exam are needed. Chronic dental infection, foreign body, and both benign and malignant sinonasal neoplasia must be included in the differential diagnosis of unilateral CRS 539 . S 1 Most of these conditions can be eliminated by a thorough physical exam including nasal endoscopy along with appropriate imaging (CT or MRI).…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…The likelihood of a final diagnosis of a benign or malignant tumor is increased approximately eight-fold in unilateral versus bilateral sinonasal disease [1,4]. IP is found in up to 17% of patients with unilateral sinus disease [2].…”
Section: Discussionmentioning
confidence: 99%
“…There are several differential diagnoses of unilateral sinus disease with or without polypoid masses in the nasal cavity and middle meatus, e.g. asymmetric manifestation of bilateral chronic rhinosinusitis, odontogenic sinusitis, (antro)choanal polyp, otherwise undefined isolated nasal polyps and benign or malignant tumors [1,2,3,4]. Tumors can mimic inflammatory lesions due to superficial edema hiding the typical endoscopic appearance of such tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative computed tomography (CT) findings may aid in this evaluation, with previous work focusing on common diagnoses for unilateral compared to bilateral disease processes. 4 , 5 For example, AFRS patients often demonstrate unilateral disease, heterogeneous opacification, and expansion of the sinuses. 6 Recently, our group and others have identified that patients with CCAD demonstrate septal and centrally located mucosal thickening on CT scan.…”
Section: Introductionmentioning
confidence: 99%